Analysis of Osteoclasts and Root Resorption in Corticotomy-Facilitated Orthodontics with Ibuprofen Administration-An Animal Study - Chanakant Jindarojanakul; Pannapat Chanmanee; Bancha Samruajbenjakun (MDPI AG, 2022)
Following corticotomy surgery, patients experience moderate to severe post-operative pain that necessitates prescriptions of analgesics. The prostaglandin inhibitory effect of ibuprofen influences the mobility of teeth during orthodontic treatment. This study aimed to determine how ibuprofen affects histological reactions and dental root resorption during orthodontic tooth movement aided by corticotomy. Forty-two male Wistar rats were divided into three groups by random selection: (1) control group, (2) corticotomy group (CO), and (3) corticotomy with 0.6 mL of 15 mg/kg ibuprofen group (CI). On each buccal and palatal alveolar bone, two decortication points were made. Orthodontic tooth movement was induced on the maxillary first molar for 21 days utilizing a NiTi-closed coil spring with 10 g of force. Hematoxylin and eosin were used to prepare and stain the histological sections. The numbers of osteoclasts on days 0, 7, 14, and 21 were determined, and the root resorption area on days 0 and 21 was measured. Compared to the control group, the osteoclast counts in the CO and CI groups were considerably greater (p < 0.002). No significant differences were observed between the CO and CI groups in the numbers of osteoclasts or the percentages of root resorption (p > 0.05). The amounts of osteoclast activity and root resorption were unaffected by the administration of ibuprofen in corticotomy-facilitated tooth movement.